Developing an analytical model for prediction of tyre rolling resistance on moist soils. (11th November 2022) - Gheshlaghi, Fatemeh; Mardani, Aref; Mohebbi, Arash; Taghavifar, Hamid
This paper presents a finite element analysis-smoothed particle hydrodynamics (FEA-SPH) technique to predict the rolling resistance of an agricultural tyre over moist soils. Firstly, dry clay-loam soil is modelled using hydrodynamic elastic-plastic materials and the water behaviour is captured using the Murnaghan equation of state. Then, to simulate moist soil, water layers are added to the dry soil surface. Soil calibration is performed based on experimental data using a bevameter and through the direct shear tests under similar operating conditions. A free-rolling bias-ply tyre (size 8.25-16) employed for the experiments was modelled using the FEA method. The interface contact between tyre and soil is described based on a node-symmetric node-to-segment contact with edge treatment. The obtained simulation results for rolling resistance account for different levels of soil moisture, traffic and vertical load. Finally, the proposed model is validated using experimental data obtained from a single-wheel tester in the controlled test condition.